Computerized Cognitive Training by Healthy Older and Younger Adults: Age Comparisons of Overall Efficacy and Selective Effects on Cognition - Ng, Nicole F.; Osman, Allen M.; Kerlan, Kelsey R.; Doraiswamy, P. Murali; Schafer, Robert J. (Frontiers in Neurology, 2021)
Among the non-pharmacological methods under development for maintaining cognitive function across the lifespan is computerized cognitive training (CCT). There has been considerable interest in using CCT to slow or remediate age-related cognitive decline, both normal and pathological. Towards these ends, it would be useful to know how the effects of CCT on cognitive function vary over the course of normal cognitive aging. Are there changes in either 1) the overall efficacy of CCT or 2) which cognitive faculties are affected? To address these two questions, we reanalyzed results from a large online study by Hardy et al. (2015) of 4715 adults between 18 and 80 that examined effects of CCT on both a neuropsychological test battery and self-reported ratings of cognition and affect in daily living. Combined across all participants, Hardy et al. found greater improvement on both types of assessment following 10 weeks of CCT with the commercial program Lumosity, as compared to practice with a control activity involving computerized crossword puzzles. The present study compared the size of these effects on the older (50-80) and younger (18-49) participants. To address the question of overall efficacy, we examined CCT effects (treatment minus control) on overall performance of the test battery and mean rating. No significant difference on either measure was found between the two age cohorts. To address the question of whether the same magnitude of overall effects on both age cohorts was due to equivalent effects on the same set of underlying cognitive functions, we examined the patterns of CCT effects across individual subtests and rated items. These patterns did not differ significantly between the two age cohorts. Our findings suggest that benefits from CCT can occur to a similar degree and in a similar way across an extended part of the adult lifespan. Moreover, the overall effects of CCT delivered over the internet were of the same small to moderate size as those typically found in the lab or clinic. Besides improving access and reducing the cost of CCT for older adults, delivery over the internet makes long-term training more practicable, which could potentially yield larger benefits.